Analysis of money and their equivalents. - Nizamdinova Kumarbay, A. A. K. (Journal of Economic Research & Business Administration, 2016)
Today the accounting of money occupies one of the central places in system of accounting in the organizations. Money is a component of current assets. As they are necessary for the enterprise for implementation of calculations between suppliers and contractors, for implementation of payments in the budget, calculations with credit founders, for delivery to workers of a salary, awards and for implementation of other types of payments. Money arrives on the enterprise from buyers and customers for the rendered services, from banks in the form of loans, from institutions and the organizations as the temporary help, etc. Management of money becomes more and more important because of huge complexity of the financial markets. Competitiveness demands that, the enterprise was able to get means for innovations and further development. The correct disclosure and classification of money and their equivalents, are necessary for an exact assessment of liquidity of the company.